UNIVERSITIES AS BEACONS OF HOPE IN AN ERA OF CHANGE (Sun’iy Intellekt Nazariyasi va Amaliyoti: Tajribalar, Muammolar va Istiqbollari, 2024)
In today's world, where we are surrounded by unprecedented challenges and breathtaking opportunities, the role of universities in shaping the trajectory of societal progress becomes increasingly crucial. Just as the Renaissance marked a period of profound transformation in European society, characterized by a resurgence of learning, creativity, and innovation, we stand today on the cusp of what some envision as a "third renaissance." This essay explores the pivotal role that universities play in laying the groundwork for such a renaissance, examining their contributions to fostering innovation, nurturing critical thinking, promoting interdisciplinary collaboration, and driving societal advancement.